2013
DOI: 10.3892/ijmm.2013.1292
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of endoplasmic reticulum stress-induced invasion and migration of breast cancer cells through the downregulation of heparanase

Abstract: Tumor metastasis is the ultimate stage of cancer, and the primary cause of mortality in patients. Tumor cells breaking through the natural barrier consisting of the basement membrane (BM) and extracellular matrix (ECM) is the a crucial step in tumor invasion and metastasis. Thus, protecting this barrier is the key to reducing mortality. Heparanase is a mammalian endo-β-glucuronidase which has been found to promote the cleavage of heparan sulfate (HS), and plays a significant role in tumor cell invasion and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…A number of studies have demonstrated that heparin induces the apoptosis of tumor cells (810), which is in accordance with the results observed in the present study. The TUNEL results demonstrated that following treatment, the tumor cells became apoptotic, in particular in the combination group (Fig.…”
Section: Resultssupporting
confidence: 93%
“…A number of studies have demonstrated that heparin induces the apoptosis of tumor cells (810), which is in accordance with the results observed in the present study. The TUNEL results demonstrated that following treatment, the tumor cells became apoptotic, in particular in the combination group (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Tumor metastasis is the cause of death of the majority of cancer patients. Previous studies have indicated that HPA expression is regulated by P53, NF-KB, and ERS to promote invasion and metastasis [23-25]. The present study focused on the relationship between GRP78 and HPA.…”
Section: Discussionmentioning
confidence: 94%
“…But, it is interesting to note that the induction of endoplasmic reticulum stress by chemotherapeutic reagents is involved in the enhanced invasion and migration ability of breast cancer cells and inhibition of heparanase (using one of these inhibitors, OGT2115) suppressed the invasion and migration ability of breast cancer cells. This provides a strong rationale for the development of heparanase-based therapeutics for the prevention of metastasis induced by chemotherapeutic reagents (161). The use of OGT2115 combined with cisplatin led to significant inhibition of cell proliferation, invasion, and migration of human nasopharyngeal cells, further suggesting that combination approaches with heparanase inhibitors may improve outcomes with existing chemotherapeutic regimens (162).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%